2021
DOI: 10.1002/ehf2.13285
|View full text |Cite
|
Sign up to set email alerts
|

Reverse remodelling by sacubitril/valsartan predicts the prognosis in heart failure with reduced ejection fraction

Abstract: Aims Despite well-established benefits of sacubitril/valsartan for cardiac reverse remodelling and the prognosis of patients with heart failure with reduced ejection fraction (HFrEF), there are some patients with limited therapeutic response, even with optimal therapy. We assessed the treatment response to sacubitril/valsartan in patients with HFrEF, focusing on the association between reverse remodelling and the prognosis. Methods and results Using a retrospective cohort of consecutive patients with HFrEF tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…It was found that in the overall population, the LVEF increased significantly by the sixth month after taking Sacubitril-Valsartan, while the LVEDD, LEVSD, LAD and LVMI decreased significantly. These results were confirmed by the previous three studies (11)(12)(13). In subgroup analysis, the improvement of heart function in male and NHYA II and III subgroups was more substantial than in women and NYHA IV subgroups.…”
Section: Discussionsupporting
confidence: 89%
“…It was found that in the overall population, the LVEF increased significantly by the sixth month after taking Sacubitril-Valsartan, while the LVEDD, LEVSD, LAD and LVMI decreased significantly. These results were confirmed by the previous three studies (11)(12)(13). In subgroup analysis, the improvement of heart function in male and NHYA II and III subgroups was more substantial than in women and NYHA IV subgroups.…”
Section: Discussionsupporting
confidence: 89%
“…Growing evidence has emerged of the role of S/V in modifying the clinical course of HFrEF patients, through its modulation of neurohormonal imbalance [2]. The effect of S/V on left chambers' remodelling has been previously demonstrated by traditional 2D TTE [1,[3][4][5][6][7]23] and speckle tracking analysis [5]. On the contrary, there is a paucity of data on the impact of S/V on RV dimensions and function, which are based exclusively on 2D echocardiographic parameters [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the case of previous myocardial infarction, the LV may undergo profound morphological changes with distortion of its 3D shape, which may be unnoticed by 2D echocardiography [27,28]. Although LV reverse remodelling has been described by 2D TTE at mid-and long-term follow-up after S/V initiation in HFrEF patients [1,[3][4][5][6][7]23], only one study conducted subgroup analyses and found no differences in the 2D LVEF improvement between IHD and non-IHD [29]. Such discrepancy from our results may be ascribed to the short followup (3 months) and the low dose of S/V achieved by patients enrolled in the study by Almufleh et al [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we compared the changes in echocardiographic parameters, which are indicative of the response to treatment, and can also translate into prognostic benefits 28 . Improvements in echocardiographic parameters were observed 1–6 months after the initiation of treatment and were maintained until 12–24 months after initiation, suggesting that the early initiation of combination therapy may result in better prognosis in diabetic patients with HFrEF.…”
Section: Discussionmentioning
confidence: 99%